Synergistic effect and antibiofilm activity of the antimicrobial peptide K11 with conventional antibiotics against multidrug-resistant and extensively drug-resistant Klebsiella pneumoniae - Chatupheeraphat, Chawalit; Peamchai, Jiratchaya; Luk-in, Sirirat; Eiamphungporn, Warawan (Frontiers in Cellular and Infection Microbiology, 2023)
Infections caused by drug-resistant Klebsiella pneumoniae are now a serious problem for public health. Therefore, new antibacterial agents or a combination of agents as the first line of treatment are urgently needed. K11 is a novel antimicrobial peptide (AMP) that has demonstrated in vitro antimicrobial activity against several types of bacteria. Additionally, K11 has previously shown no hemolytic activity. This study aimed to investigate the synergistic action of K11 in combination with different conventional antibiotics against fifteen clinical isolates of multidrug-resistant (MDR) and extensively drug-resistant (XDR) K. pneumoniae. K11 showed synergy with antibiotics against these isolates. The synergistic effects were clearly observed for K11 in combination with chloramphenicol, meropenem, rifampicin, or ceftazidime, whereas no synergy was observed when K11 was combined with colistin. The antibiofilm potential of K11 was also explored. K11 effectively prevented biofilm formation against K. pneumoniae strong biofilm producers in a concentration-dependent manner starting at 0.25×MIC and exerted an enhancing effect when administered in combination with meropenem, chloramphenicol, or rifampicin. Additionally, K11 showed high stability to temperatures, pH, serum, and salts. Significantly, K. pneumoniae showed no induction of resistance even after prolonged exposure to a sub-inhibitory concentration of K11. These findings indicate that K11 is a promising candidate with potent antibacterial and antibiofilm activities and acts synergistically with commercial antibiotics against drug-resistant K. pneumoniae.